Pengaruh Pelatihan Kerja Terhadap Kinerja Karyawan (Studi Kasus Pdam Tirta Bumi Wibawa Kota Sukabumi) - Supriatna, Apip; Sutisna, Mamun (Jurnal Riset Bisnis dan Investasi, 2016)
The fact that human resources (employee) often dominant and play an active role in organization activities is the reason why this study needs to be done. Along with the development of science and knowledge more advanced then the companies are expected to be able to make its employees more skilled and trained in doing its job. One effort that can be done to improve the performance of the company’s employees of such companies is to conduct employee training. This research uses the sampling method sampling with nonprobability saturated, while the techniques of data collection are done by doing a spread of questionnaires to the 110 respondents, The data analysis method in this research tests for assumptions of classical, descriptive analysis, correlation analysis, hypothesis test, and regression analysis. The result obtained in this study that the training provided at PDAM Tirta Bumi Wibawa Sukabumi to employees classified as good or high, performance in PDAM Tirta Bumi Wibawa Sukabumi is also good. Based on the research tha has been done, the regression equation is Y +43.163 + 0.392X. results of the study stated that in PDAM Tirta Bumi Wibawa Kota Sukabumi job training and the performance of the employees have a positive relationship of 0.396 and training work affect the performance of the employees of 15.7% and 84,3% explained by other factors by the salary, work environment, organizational culture, leadership and motivation.